2022
DOI: 10.1007/978-3-031-17143-7_11
|View full text |Cite
|
Sign up to set email alerts
|

CPU Port Contention Without SMT

Abstract: CPU port contention has been used in the last years as a stateless side channel to perform side-channel attacks and transient execution attacks. One drawback of this channel is that it heavily relies on simultaneous multi-threading, which can be absent from some CPUs or simply disabled by the OS. In this paper, we present sequential port contention, which does not require SMT. It exploits sub-optimal scheduling to execution ports for instruction-level parallelization. As a result, specifically-crafted instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…State of the art of hardware fingerprinting mechanisms focuses on detecting static CPU properties, such as the cache size or micro-architectural generation [40,29] or on the relative speed of the machine's underlying components [32,19]. This work, in contrast, focuses on the power consumption of the CPU -we assume that, due to slight manufacturing differences in the hardware, the power consumption is slightly different between each device.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…State of the art of hardware fingerprinting mechanisms focuses on detecting static CPU properties, such as the cache size or micro-architectural generation [40,29] or on the relative speed of the machine's underlying components [32,19]. This work, in contrast, focuses on the power consumption of the CPU -we assume that, due to slight manufacturing differences in the hardware, the power consumption is slightly different between each device.…”
Section: Methodsmentioning
confidence: 99%
“…We believe that this increases the robustness of our system. Rokicki et al [29] used WebAssembly instructions as a fingerprinting method, creating a method for detecting hardware processor generation based on the processor's lookahead buffer behavior. Laor et al [19] showed that it is possible to fingerprint systems based on the individual execution units found inside their Graphical Processing Units (GPUs).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation